Bioecology of Epilachna difficilis (Coleoptera: Coccinellidae: Epilachninae) in Central-West of Mexico - Garcia-Segura, Jonas; Cortez-Madrigal, Hipolito; Marin-Jarillo, Antonio; Angoa Pérez, Maria Valentina (Revista Colombiana de Entomología, 2017)
Epilachna difficilis was reported for the first time on Bonplandia geminiflora (Polemoniaceae). To study the biological and ecological aspects of this species, samples were taken weekly in 2011 in “La Gloria” Canyon, Sahuayo, Michoacán, México, and complementary studies were conducted in the laboratory. The first occurrence of E. difficilis was observed in mid-August and the last in early December. Defoliation to B. geminiflora ranged from 38.0-98.5 %. Six species of predators, viz., Podisus congrex, Podisus brevispinus, Oplomus dichrous, Oplomus pulcher (Hemiptera: Pentatomidae: Asopinae), Pselliopus nigropictus, and Rocconota sp. (Hemiptera: Reduviidae), were recorded. Temperature and precipitation were positively correlated (r = 0.8 and 0.6, respectively) with higher population peaks. However, E. difficilis showed a wide range of adaptability in different regions and climates where its host plants grow. Under laboratory conditions, five instars were recorded during 25.95 days of larval development; the entire lifecycle was completed in 37.8 ± 1.7 days. Of the five crops species evaluated, only cucumber suffered damage (30.0 %) by adult insects, although all insects died thereafter. This is the first bio-ecological study of E. difficilis. Results may be useful in the biological control of related pests such as E. varivestis.